2009
DOI: 10.1007/s10903-009-9249-4
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Participation by Parental Language Use in 4th, 8th, and 11th Grade Students in Texas, USA

Abstract: Research on physical activity (PA) by level of acculturation in Hispanic children is limited and findings have been mixed. We examined PA participation by primary language used with parents in a representative sample of 4th, 8th, and 11th grade Texas public school students. Mixed-effects regression models were conducted using cross-sectional data from the 2004-2005 School Physical Activity and Nutrition Study (n = 22,049). Self-reported PA was compared among three language-ethnic groups: Spanish-Hispanic (SH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 46 publications
3
28
3
Order By: Relevance
“…28, 29 Recent immigrants and non-English speaking youth have less structured physical activity but also less sedentary activity time. 30, 31 In our study, statistical models additionally adjusted for language spoken in the home did not result in significantly altered estimates. Thus, there was no evidence of mediation of racial/ethnic differences in behaviors by home language.…”
Section: Discussioncontrasting
confidence: 45%
“…28, 29 Recent immigrants and non-English speaking youth have less structured physical activity but also less sedentary activity time. 30, 31 In our study, statistical models additionally adjusted for language spoken in the home did not result in significantly altered estimates. Thus, there was no evidence of mediation of racial/ethnic differences in behaviors by home language.…”
Section: Discussioncontrasting
confidence: 45%
“…exercise is for young people, exercise is more for men, exercise is only for people who are healthy or really good at it, exercise conflicts with religious beliefs) might prevent some immigrants from being more physically active (Hosper et al 2008). Springer et al (2009) for instance found in a study with Hispanic immigrants that cultural values related to modesty (i.e., feeling embarrassed by how one looks in gym attire), machismo (i.e., spouses/ partners do not want women to go out and exercise with other men), and familismo (i.e., importance of putting family needs before one's own needs, housework responsibilities) were important barriers preventing regular physical activity. Similarly, Kloetze (2001) reported that married Turkish women in the Netherlands only left the house when they could take their children with them due to responsibility for house and children.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, immigrant parents may place higher value on children's time devoted to reading and learning activities, language lessons, academic performance, and participation in family activities. Safety concerns are another important consideration that may interact with gender-specific cultural values of heightened parent protectiveness for minority girls (Springer et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Singh, Yu, Siahpush, and Kogan (2008) reported that immigrant youth with less acculturation 10 were more likely to be physically inactive and also were less likely to participate in youth sports than native youth. Researchers have also found that Hispanic populations who were more proficient in using English engage in more physical activity than those with limited English proficiency (Lopez-Quintero, Berry, & Neumark, 2009;Springer et al, 2010). Further Lopez-Quintero et al (2009) found that Hispanics who were proficient in the English language were 50% more likely to receive advice about physical activity than Hispanic populations with limited English proficiency.…”
Section: Ells In Context Of Physical Activity and Health: Disparitiesmentioning
confidence: 99%